Efficacy of a stannous fluoride dentifrice for relieving dentinal hypersensitivity in Chinese population: an 8-week randomized clinical trial - Li, Rui; Yang, Wenjie; Grimaldi, Roberta; Zeng, Peter; Smith, Gary; Chen, Xi (Clinical oral investigations, 2024)
Objectives To compare the effectiveness of using a 0.454% stannous fluoride-containing dentifrice twice daily in relieving dentinal hypersensitivity (DH) in a Chinese population. Materials and methods This was a single-centre, randomized, controlled, examiner-blind, three-treatment-arm, parallel-group study in participants with clinically diagnosed DH. Subjects who met inclusion criteria (n = 197) were randomly allocated into 3 groups: test group (n = 66)—using a 0.454% stannous fluoride-containing dentifrice twice daily; positive control group (n = 64)—using a 5.0% calcium sodium phosphosilicate-containing dentifrice twice daily; negative control group (n = 67)—using a 1150 ppm of NaF dentifrice twice daily. Status of DH was assessed at week 4 and week 8 by the same independent examiner. Changes from baseline in Schiff sensitivity score, tactile threshold and Dentine Hypersensitivity Experience Questionnaire (DHEQ) score were analysed using analysis of covariance models. The DHEQ evaluated subject-perceived oral health-related quality of life (OHRQoL). Results Statistically significant improvements in mean Schiff scores (p < 0.0001 for all products at Weeks 4 and 8), tactile threshold (p < 0.0001 for test and negative control at Weeks 4 and 8: Week 4 p = 0.0040 and Week 8 p < 0.0001 for positive control) and all DHEQ scores (p < 0.01 for all groups) were observed. No statistically significant differences were observed in the adjusted mean between all dentifrices at both timepoints, potentially driven by a placebo effect. Forty-two treatment-emergent adverse events (TEAEs) were reported (n = 32 subjects), with 2 serious AEs (n = 1) in the test group. TEAEs were not considered treatment-related. Conclusions All groups demonstrated statistically significant improvements in Schiff score, tactile threshold and OHRQoL. However, due to a possible placebo effect in the negative control, there were no statistically significant differences between the dentifrices. Clinical relevance This study adds to the growing research exploring why the placebo effect is a common phenomenon in DH studies. Trial registration: ClinicalTrials.gov Identifier: NCT04950465.